CONTENTS AND MEANINGS OF " UTOPIA " WRITTEN BY THOMAS MORE - Mamaziyayeva Odina; Usmanova Sevara Sultanovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
A"Utopia" by Thomas Mora, a summary of which is in this article, became the nominative for the entire genre of the English writer and lawyer. The book was first published in 1516. Its full name is "The Golden Book", which is very funny, about the best device of the state and the best device of the new "Utopia" Thomas More was born in London in 1478 in a wealthy civil family, raised in the house of a prominent political figure of the time. Morning was first engaged in the study of Greek philosophy and literature for two years at the University of Oxford, he entered the circle of the Oxford Asicalist, he, and then firmly Father - a famous royal judge, seven years of legal studies in special schools of English legists there was. Thomas Mora’s Utopia is distinguished from other works by its many and essence The work is very interesting and clearly written. This work is considered a long-awaited work for that time, that is, a work of striving for equality and the future